SAFE AND DANGEROUS TUMORS OF THE FEMALE SEX (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Tumor (tumor, swelling, cancer) is a pathological process, which is a change or violation of the normal growth, development of tissues and cells in the body. As a result of such a chaotic growth, the activity of the organs changes and is disturbed. Until now, the causes of tumors and their etiopathogenesis are unknown. Scientists have different views on tumor etiopathogenesis. This article provides information about safe and dangerous tumors of female genital organs.